Enhancing Nutritional Composition and Glycemic Index of Traditional Wheat Couscous Through Agglomeration With Algerian-Grown Quinoa Semolina - Bendaoud, Saliha; Belkacemi, Louiza; Tugen, Aslihan; Ozgolet, Muhammed; Arici, Muhammet; Bouchama, Abdelghani (WILEY, 2026)
This study investigated the feasibility of replacing wheat semolina with semolina produced from Algerian-grown quinoa in making Algerian traditional couscous across substitution rates of 0%, 50%, 75%, and 100%. Couscous samples were analyzed for their proximate composition, fatty acid (GC-FID) and mineral (Inductively Coupled Plasma-Optical Emission Spectrometry [ICP-OES]) composition, cooking quality, microstructure, and in vitro glycemic index. Incorporating higher levels of quinoa (75% and 100%) into the couscous enhanced protein (13.72% +/- 0.15% and 14.87% +/- 0.36%, respectively) and fiber contents (1.69% +/- 0.19% and 4.96% +/- 1.20%, respectively) compared to wheat-based couscous (9.22% +/- 0.01% and 0.32% +/- 0.27%, respectively). The baseline wheat couscous values for zinc (1.49 +/- 0.02 mg/100 g), iron (2.74 +/- 0.09 mg/100 g), and magnesium (42.00 +/- 6.22 mg/100 g) increased proportionally with substitution levels, reaching 4.63 +/- 0.10, 8.09 +/- 0.30, and 209.34 +/- 4.74 mg/100 g, respectively, in the whole quinoa couscous formulation (p < 0.001). The long-chain omega-3 fatty acids docosahexaenoic (DHA) and eicosapentaenoic (EPA) were detected only in the 100% quinoa couscous (8.06 +/- 0.01 and 22.03 +/- 0.03 mg/100 g, respectively). The cooking quality of the 50% quinoa couscous was the closest to that of wheat-based couscous. The lowest glycemic index value was observed with 75% (63.04 +/- 0.09) and 100% (61.26 +/- 0.52) quinoa level substitution. Quinoa substitution improved the nutritional quality while maintaining relatively the culinary properties of couscous. It enhanced its health-promoting potential, supporting its use as a sustainable food, in particular for gluten-free diets. Practical Applications Incorporating quinoa into couscous formulations not only enhanced the nutritional quality but also increased the polyunsaturated fatty acid (PUFA) ratio and levels of essential fatty acids. Moreover, with the current dietary focus on nutrient-dense foods, quinoa-enriched couscous aligns well, as it contains more proteins, dietary fiber, PUFA, and micronutrients than traditional wheat-based couscous. Whole quinoa couscous provides a naturally gluten-free alternative, making the product more appealing to a wider consumer base, which may be of a great interest for industrial food producers and consumers.
Keywords: Algerian-grown quinoa; fortification; glycemic index; scanning electron microscope (SEM); traditional couscous; FATTY-ACID; FLOUR; QUALITY; WILLD.; BREAD; DIGESTIBILITY; BUCKWHEAT; CROPS; GRAIN; PASTA; Food Science & Technology